The Influence of Work Motivation and Workload on Employee Performance: Literature Review - Exabiaggi, Rizal Dhani; Awalludin, Muhammad As’ad; Ramdani, Alif Dimas; Hasin, Farid Bima; Putra, Riyan Sisiawan (Journal of International Accounting, Taxation and Information Systems, 2024)
In a company, employees are one of the most important elements in achieving company goals. An employee's performance is certainly influenced by several factors that a manager needs to know. Managers must know the strengths and weaknesses of each manager in order to maximize potential and minimize employee deficiencies. Motivation is one of the things that influences human behavior. Motivation is also called a driver, desire, supporter or need, a need that can make someone enthusiastic and motivated to reduce. This research aims to find out whether there is an influence of motivation and workload on employee performance.